PEREMPUAN PEMBUAT BATU MERAH DI DESA LANGGEA KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Winda Herlianty; La Ode Topo Jers; Hasniah Hasniah (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2019)
This study aims to find out and describe the involvement of women in the process of making bricks and the strategies of women who make brick in maintaining their business and work. This study uses the theory of feminism by Naomi Wolf (1997) and Bennet's (2005) adaptation strategy theory, using the Ethnographic method. The results showed that the involvement of women in the process of making red stone in Langgea Village was at almost every stage of the process of making red stone, which starts from extracting raw materials, making dough, printing bricks, drying, making bricks, burning until selection or selection red stone (burying). There are various strategies applied by female workers in maintaining their businesses and jobs, both business owners and workers. The business owner's strategy is to choose the right location, pay attention to the quality of the red stone, and be able to market the red stone well. While the strategy of workers is to establish trust with business owners and can discipline them in work.